Carbonate platform demise across the Triassic-Jurassic transition in the Qiangtang Basin, Tibetan Plateau - Zou, Yi; Wei, Hengye; Mansour, Ahmed; Wen, Yue; Fu, Xiugen (Frontiers in Marine Science, 2025)
IntroductionCarbonate platforms are highly sensitive to environmental, climatic, and oceanographic changes. The demise of carbonate platform is often associated with perturbations in oceanic chemistry and/or sea level rise, which are also the modern environmental challenges for human being. However, the main causes behind the carbonate platform demise are still a matter of significant debate.MethodsHere, we present nitrogen (δ15Nbulk) and carbon isotopes of bulk carbonate (δ13Ccarb) and organic (δ13Corg) geochemistry data, mercury (Hg), pyritic framboids size distributions, and major element content, from the upper Sobucha Foramtion (Upper Triassic) to the lower Quse Formation (Lower Jurassic) in the Wenquan section of the Qiangtang Basin (Tibet) of the eastern Tethyan domain.ResultsThe results show that the carbonate platform demise was preceded by a negative excursion of δ15Nbulk and severe reducing, mainly euxinic conditions in shallow marine settings before the Triassic-Jurassic (T-J) boundary. This was followed by a negative excursion of carbon isotope data, coincident with an extremely positive shift in mercury composition at the T-J boundary.DiscussionThe nitrogen excursion suggests that eutrophication, likely resulting in partial assimilation of nitrogen, and euxinia in the euphotic zone may have depressed the ecosystem prior to the demise of carbonate platform. Conversely, δ13C excursion and elevated Hg levels reveal that large-scale isotopically light carbon emissions probably controlled by widespread volcanism of the Central Atlantic Magmatic Province (CAMP) were the ultimate trigger of the carbonate platform demise.